Association between ANRIL polymorphisms and risk of obsessive-compulsive disorder. Issue 3 (March 2023) - Akbari, Mohammadarian; Hussen, Bashdar Mahmud; Eslami, Solat; Neishabouri, Seyedeh Morvarid; Ghafouri-Fard, Soudeh
Abstract: Obsessive-compulsive disorder (OCD) is a disorder in which genetic factors participate. ANRIL is an example of long non-coding RNAs with crucial roles in the pathoetiology of multifactorial disorders, including neuropsychiatric conditions. We appraised association between rs1333045, rs1333048, rs10757278 and rs4977574 polymorphisms and OCD in Iranian population. There were no remarkable differences in allele and genotype distribution of rs1333045, rs1333048, rs4977574, and rs10757278 between OCD Patients and normal controls. However, the CCGG haplotype (equivalent to rs1333045, rs1333048, rs4977574 and rs10757278, respectively) has been shown to decrease risk of OCD (OR (95% CI) = 0.57 (0.39–0.85), P value-0.006 and FDR q-value = 0.041). On the other hand, TCGA haplotype has been found as a risk haplotype for OCD (OR (95% CI) = 5.17 (1.44–18.55), P value = 0.005 and FDR q-value = 0.041). In brief, the current study indicates association between two ANRIL haplotypes and risk of OCD in Iranian people.